1997
DOI: 10.1021/ic960794b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and NMR Studies of Three Pyridine-Containing Triaza Macrocyclic Triacetate Ligands and Their Complexes with Lanthanide Ions

Abstract: The synthesis of three triazamacrocycles containing the pyridine moiety and three acetate pendant arms (PCTA) is reported. The three systems differ due to the number of carbon atoms in the macrocyclic ring forming ligands PCTA-[12], -[13], and -[14], endowed with different coordination capabilities toward lanthanide(III) ions. Microscopic protonation sequences for the three ligands have been investigated by (1)H NMR spectroscopy. Complexes of PCTA-[12], -[13], and -[14] with La(III), Gd(III), and Lu(III) have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
121
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(128 citation statements)
references
References 35 publications
7
121
0
Order By: Relevance
“…[8] By reacting 2 with the commercially available 2,6-bis(chloromethyl) pyridine in refluxing anhydrous MeCN in the presence of anhydrous K 2 CO 3 , the macrocycle 1 was obtained in 85% yield after purification. The experimental conditions adopted here represent a modification [9] of the Richman-Atkins protocol. Crystals suitable for an X-ray structural determination were obtained by crystallization of 1 from a dichloromethane-toluene solution (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[8] By reacting 2 with the commercially available 2,6-bis(chloromethyl) pyridine in refluxing anhydrous MeCN in the presence of anhydrous K 2 CO 3 , the macrocycle 1 was obtained in 85% yield after purification. The experimental conditions adopted here represent a modification [9] of the Richman-Atkins protocol. Crystals suitable for an X-ray structural determination were obtained by crystallization of 1 from a dichloromethane-toluene solution (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the fitted value of t M 310 is smaller for Gd-cyclo-PCTA12 (34 ns), indicating that the rigidification and consequently the crowding of the ligand around the gadolinium induced a shortening of the residence lifetime of the inner-sphere water (14,15). It is worth mentioning that the introduction of the pyridine moiety in the macrocycle skeleton already resulted in a first shortening of the residence lifetime of the inner-sphere water, as demonstrated by comparing the t M value of two q ¼ 2 complexes, Gd-DO3A (t M 298 ¼ 160 ns) and Gd-PCTA12 (t M 298 ¼ 70 ns) (24), and that the introduction of a second cycle induces a further shortening of the residence lifetime of the inner-sphere water, probably by elongating of the Gd-H 2 O bond. A theoretical calculation based on the Solomon-Bloembergen-Morgan theory of paramagnetic relaxation has shown that the optimal residence lifetime of the inner-sphere water to attain the highest relaxivities is around few tenths of a nanosecond (2).…”
mentioning
confidence: 88%
“…It is generally assumed that this improvement is due to the presence of two water molecules (q ¼ 2) in the inner sphere as demonstrated by relaxivity study, variable-temperature NMR studies of the lanthanum and lutetium complexes (24,25) and luminescence lifetime measurement of europium and terbium complexes (25). Although PCTA12 is a heptadentate macrocyclic ligand, its gadolinium complex is characterized by a high thermodynamic stability (logK Gd 3þ ¼ 20.8) (25).…”
mentioning
confidence: 99%
“…III Complexes: The general procedure for the synthesis of the gadolinium complexes consists of the addition of equimolar amounts of the corresponding ligand (2 mmol) and GdCl 3 ·6H 2 O (2 mmol) in deionized water (20 cm 3 ), followed by adjustment of the pH to 6.0 by adding KOH.…”
Section: Synthesis Of Gdmentioning
confidence: 99%